HUKUM SUKARELAWAN DALAM PENGATURAN LALU LINTAS BERDASARKAN UNDANG-UNDANG NOMOR 22 TAHUN 2009 - Lauren, Audrey; Sudiro, Ahmad (Legal Standing : Jurnal Ilmu Hukum, 2024)
This research aims to examine the implementation of legal freedom in traffic regulation in accordance with applicable regulations and the challenges faced in the field. This research adopts a type of sociological juridical research, which aims to examine various rules, concepts, societal views and legal doctrines sourced from secondary legal materials and relevant laws and regulations, especially those related to the issues discussed. The design approach implemented in this research is none other than statutory regulations or a statutory approach. This research was achieved through efforts to analyze regulations or forms of regulations which were characterized as being related to the legal context issues. The data collection technique in this research uses secondary data, where information is obtained from library research, by tracing, collecting and analyzing the required literature materials. Researchers use legal analysis techniques which are followed by efforts at description, systematization, legal analysis and interpretation. The results of this research reveal that there is no ban on volunteer road crossing/traffic controllers, however, on the one hand, there have been several complaints from the public that the presence of these volunteers can disrupt and hinder their traffic. However, if the volunteer worker is proven to have caused a traffic accident, then it must be processed in accordance with applicable criminal law. In many areas, volunteers have demonstrated their ability to help regulate traffic flow, but support from the government is low and remains a challenge for communities. Therefore, there is a need for training and training for volunteer workers, supported by increased monitoring and evaluation of volunteers.